Comparison of radio frequency identification tag housings in a tropical forestry work environment. Issue 4 (2nd October 2019) - Kaakkurivaara, T.; Kaakkurivaara, N.
ABSTRACT: Precise information on the origin of timber can be obtained by using an identifier system, which can help in preventing illegal logging, managing timber supply chains and increasing value adding. Radio frequency identification (RFID) is increasingly used in log-tracking systems. The RFID tags currently available on the market are not directly suitable for forestry applications, however, unless the tags are protected by a housing. Harsh working environments mean that tag housings must be robust in order to keep their valuable information safe throughout a logging operation. The aim of this study was to provide a testing method for use as a decision-making tool by RFID users. The study used five tests to evaluate the applicability of eight kinds of tag housing for forestry applications. The tests considered climatic aspects, mechanical stress, readability and survival in the field. The method was found to work well with tested tag housings, revealing their strengths and weaknesses. Using the testing method, a procedure is recommended to determine the most appropriate tag housing.